1972
DOI: 10.1128/am.24.1.31-33.1972
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a Transport Medium for the Recovery of Aerobic and Anaerobic Bacteria from Applicator Swabs

Abstract: The survival of four aerobic and four anaerobic pathogens was evaluated quantitatively on cotton swabs and calcium alginate swabs stored in dry tubes as compared with swabs stored in Amies Transport Medium without charcoal. Survival of the pathogens was markedly improved when stored in Amies Transport Medium, although there was considerable loss of viability after a few hours of storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…Since oxygen is by definition toxic for anaerobic bacteria, a number of devices have been developed to minimize air exposure of specimens. These include transport tubes containing oxygen-free gas, specialized transport media, and even portable anaerobic chambers (1,2,4,6,9). Although such precautions appear meritorious, there are no data available to document efficacy except with specimens transported on swabs.…”
Section: Resultsmentioning
confidence: 99%
“…Since oxygen is by definition toxic for anaerobic bacteria, a number of devices have been developed to minimize air exposure of specimens. These include transport tubes containing oxygen-free gas, specialized transport media, and even portable anaerobic chambers (1,2,4,6,9). Although such precautions appear meritorious, there are no data available to document efficacy except with specimens transported on swabs.…”
Section: Resultsmentioning
confidence: 99%
“…In our study only 1 (1%) of 75 anaerobic strains was lost over this time period in SGT, and none was lost (0%o) in the FGT and SCB systems. Laboratory evaluations of anaerobic transport systems that used stock cultures generally found heavy die-off of anaerobes in controls exposed to ambient air for 4 to 24 h, and much less in transport systems that were designed to maintain anaerobiosis (1, 3,5,6,15,20,21). And Hallander et al (11), studying specimens from peritonsillar abscesses, encountered marked loss of anaerobic strains in two aerobic transport media, but excellent recovery in evacuated syringes and in gassed-out tubes containing prereduced salt solution.…”
Section: Twentymentioning
confidence: 99%
“…The use of gassed-out tubes (1, 5, 7-9, 11, 12, 17, 18), swabs in Cary and Blair transport medium (8,9,18), and swabs in gassed-out tubes (12) have been recommended and are widely used in many clinical laboratories. Several of these and other transport systems have been studied using stock cultures under conditions simulating clinical use (1, 2, 3,5,6,20,21); however, little information is available regarding their performance with clinical specimens. This study was undertaken to evaluate the ability of three common transport systems to maintain the viability of anaerobic bacteria in specimens from a wide variety of clinical infections, over a 48-h period.…”
mentioning
confidence: 99%
“…Gastrin et al (11) observed growth of C. perfringens suspended in phosphate buffer solution with swabs held in VMG II transport at room temperature. Other workers, however, did not note proliferation in simulated samples held in transport media or in dry gassed-out tubes filled with carbon dioxide (2,25).…”
mentioning
confidence: 96%
“…An identical protocol was followed for the tubes and vials held in the refrigerator. Abbreviations: H, high concentration of bacteria; L, low concentration of bacteria; (2), procedure was run in duplicate; A, PAC used as recommended by the manufacturer; B, vented in an anaerobic glove box; C, vented in air; D, plain vial vented in the glove box; E, plain vial vented in room air. inoculated with 1.0 ml each of high and low concentrations of the bacterial ceil suspensions, as was done with the PAC vials, and vented with 18-gauge cottonplugged hypodermic needles.…”
mentioning
confidence: 99%